Fire retardant treatment of low contamination for panels made from recycled plastic films and polyester resin - Gaggino, Rosana (2017)
The aim of this research was to propose a fire retardant treatment with low contamination additives for panels manufactured with recycled plastics from packaging of food industries and polyester resin. The panels made with this technology are more ecological than the traditional ones, made with shavings and fibers of wood, because they incorporate plastic wastes as raw material instead of natural resources. Because of the likely deterioration of the panel when exposed to UV-Radiation in outdoor application, they are recommended to inside buildings as coating walls and the manufacture of furniture, whereby they have to comply with the class RE-3 “low flame propagation material”, according to IRAM 11910-3:1994, NBR 9442: 1986 and ASTM E 162: 1994 Norms. Several fire retardant treatments were tested, and their influence on the flexural resistance of the panels. By other hand, a comparative study of costs was performed between the panels commercially available, and the panels developed with this technology. The use of HT-E free of halogens is proposed, which obtains a classification RE-3 and not significantly alter the flexural resistance of the panels.